1995
DOI: 10.1074/jbc.270.40.23653
|View full text |Cite
|
Sign up to set email alerts
|

Flavinylation of Monoamine Oxidase B

Abstract: Monoamine oxidase B (MAO B)The major amine-degrading enzymes in the central nervous system and peripheral tissues of mammals are monoamine oxidase A and B (MAO 1 A and B, amine:oxygen, oxidoreductase (deaminating, flavin-containing), EC 1.4.3.4). These isozymes are integral proteins of the outer mitochondrial membrane (1) and can be distinguished by differences in substrate preference (2), inhibitory specificity (3), tissue and cell distribution (4 -6), and immunological properties (7-9). Furthermore, comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 31 publications
4
28
0
1
Order By: Relevance
“…In general, several roles can exist for the covalent linkage(s) between a protein and its flavin cofactor (22)(23)(24). For MAO-A and MAO-B, the role of the covalent flavin linkage has been extensively studied (25)(26)(27)(28)(29), and the effect of replacing the linking cysteine residue (Cys-406 in MAO-A and Cys-397 in MAO-B) has been investigated (30,31). These mutagenesis studies revealed that, while replacement of the cysteine prevents covalent FAD incorporation, the covalent flavin linkage is not essential for catalytic activity, neither for targeting and insertion of the protein in the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In general, several roles can exist for the covalent linkage(s) between a protein and its flavin cofactor (22)(23)(24). For MAO-A and MAO-B, the role of the covalent flavin linkage has been extensively studied (25)(26)(27)(28)(29), and the effect of replacing the linking cysteine residue (Cys-406 in MAO-A and Cys-397 in MAO-B) has been investigated (30,31). These mutagenesis studies revealed that, while replacement of the cysteine prevents covalent FAD incorporation, the covalent flavin linkage is not essential for catalytic activity, neither for targeting and insertion of the protein in the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Site-directed mutagenesis has been used to identify specific amino acid residues (glutamate and tyrosine) in a region of M A 0 B located near the amino terminus that participate in the non-covalent binding of FAD [14, 1.51. Furthermore, changes of glutamate to aspartate, glutamine or alanine can affect covalent flavinylation of M A 0 B [16]. Also, hybrids of M A 0 A and M A 0 B have been examined in attempts to identify which amino acids or regions of the molecule might confer isozyme specificity [17].…”
mentioning
confidence: 99%
“…14 C]FAD was synthesized by a modified method of Manstein and Pai (22) as described previously (18).…”
Section: Synthesis Of [ 14 C]fad-[mentioning
confidence: 99%
“…This dinucleotide-binding site is observed in many flavoproteins with diverse functions and is thought to consist of a ␤ 1 -␣-␤ 2 motif (19), in which the terminal glutamate (Glu 34 ) interacts with the 2Ј-hydroxyl group of the ribose moiety of FAD. Site-directed mutagenesis studies, which replaced Glu 34 with alanine, aspartate, or glutamine, resulted in a dramatic loss of FAD coupling and, consequently, a corresponding loss of MAO B enzymatic activity (1,18). A second FAD-binding region was found adjacent to the dinucleotide-binding motif in MAO B (residues 39 -46 in human MAO B).…”
mentioning
confidence: 99%
See 1 more Smart Citation